Efficacy of collagenase Clostridium histolyticum in men with congenital penile curvature. (12th January 2023) - Kulkarni, Yogesh; Green, Benjamin; Pattillo, Curtis; Stirland, Isaac; Flores, Ashley; Ziegelmann, Matthew; Kohler, Tobias; Helo, Sevann; Trost, Landon
Abstract: Background: Collagenase Clostridium histolyticum (CCH) has been proven effective in multiple subpopulations of PD men; however, no studies have evaluated its role with congenital penile curvature (CPC). Aim: To evaluate the safety and efficacy of CCH in men with CPC. Methods: A prospective registry was queried of men undergoing CCH injections at our institution. Beginning in 2016, CCH was administered to CPC men using a similar protocol to PD. A comparative analysis was performed between cohorts to evaluate the safety and efficacy of therapy. Outcomes: Objective measures included penile length and curvature, while subjective outcomes included standardized (International Index of Erectile Function and Peyronie's Disease Questionnaire) and non-standardized assessments. Curvature outcomes were categorized as follows: 1 – included all men, with the most recent assessment considered final, and 2 – only men who had completed eight CCH injections or stopped early due to satisfaction. Results: From 2014 to Oct 2021, a total of 453 men (408 PD, 45 CPC) underwent one or more CCH injections. In comparing cohorts, CPC men were younger (33 vs 58 years, p<0.0001), had lesser baseline curvatures (52.5 vs 65°, p<0.01), more ventral curves (25.7 vs 9.2%, p<0.01), and longer penile lengths (12.5 vs 12.0 cm, p=0.04). Following treatment, both cohorts experienced similar curvature improvements. Specifically, PD men experienced 20-25° or 33-35% improvements depending on definition compared to 25-30° or 40-50% in CPC men (all p-values >0.05). CPC and PD men also demonstrated similar changes on standardized questionnaires, with the exception of the Psychological and Physical subdomain, which was more improved in CPC men (-11 vs -4, p<0.01). Baseline curvature was positively correlated with greater absolute (degree) and relative (percent) improvements. Adverse events were similar between groups after controlling for confounders. Clinical Implications: CCH may be safely and effectively administered in men with CPC. These data provide the first evidence for the efficacy of a non-surgical therapeutic option in this cohort. Strengths and Limitations: Strengths – large, prospective series with standardized assessments; Limitations - non-randomized study, short-term follow-up, and lack of standardized method to differentiate CPC from PD. Conclusions: CCH may be safely and effectively administered to men with CPC, with similar success rates compared to PD. Increasing curvature was associated with greater absolute (degree) and relative (percent) improvements, supporting the role for CCH in men with mild, moderate, or severe curvatures. External validation is warranted prior to routine implementation.